2018
DOI: 10.1002/hed.25558
|View full text |Cite
|
Sign up to set email alerts
|

Utility of adjuvant chemotherapy in patients receiving surgery and adjuvant radiotherapy for primary treatment of esthesioneuroblastoma

Abstract: Background Past research established that surgery plus adjuvant radiotherapy (S + AR) improves overall survival (OS) in esthesioneuroblastoma (ENB). However, it is unknown if the addition of adjuvant chemotherapy (AC) further improves survival. The primary objective of this study was to compare survival among patients treated with S + AR alone to patients who underwent S + AR + AC. Methods Retrospective review of patient records. Results Thirty‐eight patients met inclusion criteria for either S + AR or S + AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The role of chemotherapy is still controversial in ENB, generally used for advanced, high-grade tumors (22)(23)(24). However, chemotherapy did not improve OS, RFS or DSS (25,26). In advanced tumors, we therefore support multimodal therapy.…”
Section: Discussionmentioning
confidence: 76%
“…The role of chemotherapy is still controversial in ENB, generally used for advanced, high-grade tumors (22)(23)(24). However, chemotherapy did not improve OS, RFS or DSS (25,26). In advanced tumors, we therefore support multimodal therapy.…”
Section: Discussionmentioning
confidence: 76%
“…The current treatment strategy in adults includes surgery followed by radiation therapy . Chemotherapy might be used in case of high‐grade, recurrent, or locoregionally advanced tumors . In pediatric cases, chemotherapy combined with surgery and radiotherapy (RT) is often the treatment of choice in advanced diseases compared to adult ones .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Chemotherapy might be used in case of high-grade, recurrent, or locoregionally advanced tumors. [17][18][19] In pediatric cases, chemotherapy combined with surgery and radiotherapy (RT) is often the treatment of choice in advanced diseases compared to adult ones. 3,6 The incidence of cervical node metastases is about 10% at diagnosis but can increase to 20% during the disease in adults.…”
mentioning
confidence: 99%
“…While it is now established that surgery plus adjuvant radiotherapy is associated with superior survival in ENB, 2,5,6 there is still a question regarding the optimal use of chemotherapy after surgery. [7][8][9]21 Given that ENB can recur years after surgery, there is great interest in determining the optimal consolidation treatment that balances toxicity with efficacy to eradicate minimal residual disease. Further, there are biological characteristics of ENB, including tyrosine kinase mutations and BCL-2 dependency-which could be leveraged to develop more effective chemotherapy strategies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6] Several studies have shown that ENB is sensitive to platinum-based chemotherapy, 7,8 but the impact of chemotherapy before and after surgery on overall survival (OS) for patients with localized disease is less clear. 1,8,9 Nonspecific symptomatology, such as nasal airway obstruction, anosmia, and epistaxis, frequently delays diagnosis in ENB. 10 Consequently, patients can present with locally advanced disease infiltrating the skull base that may appear unresectable on neuroimaging.…”
Section: Introductionmentioning
confidence: 99%